Application of method of differential scanning calorimetry is for the study of mechanism of gelation of composition on the basis of carbonanotube - Привалко, Е. Г.; Дінжос, Р. В.; Рехтета, М. А.; Ващук, А. В. (Proceedings of National Aviation University (archive), 2013)
By differential scanning calorimetry method have been studied influence of nanotubes upon structure mechanism of gelation of composition. It is shown that particles of carbonanotube are active nucleation agents for crystallization of polipropilen. Crystallization takes place on the mechanism of the strained matrix. After by the got results, at content of carbonanotube of 1-2 % there are the best terms for crystallization of polymeric matrix